RETROfit of post-war housing quarters. - Hujvan, Anaztazia (Forum Landschaftsplanung - AbsolventInnenverband, 2020)
Remaking the built environment is one of the biggest challenges of our generation. Well-planned, post-war residential areas offer the greatest working environment for transformation to more sustainable urban development, adaption to climate change in the city and to a better quality of life. Academic projects "Retrofit_20" and "Urban Density Lab Lviv 2019" open up new visions for the retro-fitting oft post-war quarters in Vienna and Lviv.
Keywords: Nachhaltige Stadtentwicklung; Nachkriegsarchitektur; Stadtquartier; Stadterneuerung; Fallbeispiel